GDT315 : Print design project / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2021)
This course is an extension of knowledge in the scope of print design, in the sense that the student will produce and apply visual design solutions using actual project-based learning. The students are required to prepare problem-solving cases using the skills and techniques that they acquired. Students will take part in identifying visual problems, decision making, organizing ideas, developing visual design concepts, and execute visual solutions through producing print design campaigns. In accordance with the course requirement, students are required to create one solution/direction from several choices of print design components, and complete comprehensive visual and design planning to execute a print promotional campaign for the completion of the course.